2019
DOI: 10.5194/acp-2018-667-ac1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Responses to Referee #1’s comments

Abstract: In situ aircraft measurements obtained during the VAMOS (Variability of the American Monsoons) Ocean-Cloud-Atmosphere-Land Study Regional Experiment (VOCALS-REx) field campaign are analyzed to study the aerosol-cloud interactions in the stratocumulus clouds over the southeastern Pacific Ocean (SEP), with a focus on three understudied topics (separation of aerosol effects from dynamic effects, dispersion effects, and turbulent entrainmentmixing processes). Our analysis suggests that an increase in aerosol conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…From this result, it can be concluded that Na 2 SnO 3 is a phase-forming corrosion inhibitor. 81,82 The content of these insoluble salts in the corrosion product layer formed from the solution with mixed inhibitors was higher compared to that formed from the solution with single Na 2 SnO 3 . On the other hand, the characteristic peaks of Mg for the corrosion product layers formed from NaCl solution with mixed inhibitors was stronger (region highlighted in light grey), indicating that the thinner product layer was formed on the AZ61 alloy surface, or the oxidation state component of the product layers deposited on the AZ61 surface was significantly reduced, i.e., the existence of CMCS suppressed the oxidation of the AZ61 surface and further protected the AZ61 substrate from corroding.…”
Section: Weight Loss Measurementsmentioning
confidence: 95%
“…From this result, it can be concluded that Na 2 SnO 3 is a phase-forming corrosion inhibitor. 81,82 The content of these insoluble salts in the corrosion product layer formed from the solution with mixed inhibitors was higher compared to that formed from the solution with single Na 2 SnO 3 . On the other hand, the characteristic peaks of Mg for the corrosion product layers formed from NaCl solution with mixed inhibitors was stronger (region highlighted in light grey), indicating that the thinner product layer was formed on the AZ61 alloy surface, or the oxidation state component of the product layers deposited on the AZ61 surface was significantly reduced, i.e., the existence of CMCS suppressed the oxidation of the AZ61 surface and further protected the AZ61 substrate from corroding.…”
Section: Weight Loss Measurementsmentioning
confidence: 95%